Assessment of hormonal alterations in major depressive disorder: A clinical study. Issue 4 (20th May 2019) - Asadikaram, Gholamreza; Khaleghi, Ezetollah; Sayadi, Ahmadreza; Foulady, Shahnaz; Ghasemi, Mohammadreza Seyed; Abolhassani, Moslem; Garrusi, Behshid; Nematollahi, Mohammad Hadi
Abstract: Major depressive disorder (MDD) is a severe mood disorder that may lead to use of drugs, alcohol, and even suicide in acute cases. It has been shown that neurotransmitters and hormones have the same receptors and pathways in the mood area of the brain. Therefore, metabolic and biochemical changes are expected in MDD and, in such diseases, understanding the hormonal alterations would be extremely helpful in the management or treatment with hormone replacement therapy. We evaluated levels of cortisol, adrenocorticotropic hormone (ACTH), testosterone, thyroid‐stimulating hormone (TSH), thyroxine (T4), triiodothyronine (T3), free thyroxine index (FT4I), T3 resin uptake (T3RU), and dehydroepiandrosterone sulfate (DHEA‐S) in 79 patients suffering from MDD and 71 healthy controls. The existence of MDD was confirmed by a face‐to‐face structured clinical interview. We started the investigation by taking a blood sample from the study population. Then, hormone levels were measured by enzyme‐linked immunosorbent assay. Significant differences were found between TSH, FT4I, DHEA‐S, ACTH, testosterone, and cortisol/DHEA‐S ratio in MDD patients compared to the healthy controls. We also demonstrated a correlation between MDD recurrence and FT4I index and TSH, respectively. Regarding some hormonal changes in patients with MDD, hormonal shifts should be considered in the treatment or management of MDD patients.